Descriptive, analytical and molecular epidemiology of pancreatic cancer - O. V. Shangina; D. M. Maximovich; D. G. Zaridze (Сибирский онкологический журнал, 2022)
The purpose of the study was to present current data on the role of lifestyle and heredity factors in the etiology of pancreatic cancer (PC). Material and Methods. A systemic literature search was conducted using Medline and Elibrary databases. Results. Pancreatic cancer is the 9th leading cause of cancer-related deaths worldwide. PC has an extremely poor prognosis. The 5-year survival rate of patients with PC does not exceed 9 %. The highest incidence and mortality rates from PC are found in Eastern Europe, including Russia. The incidence of PC in 2019 was 9.3 per 100,000 males and 5.7 per 100,000 females. In Russia, PC incidence and mortality rates in both males and females show a steady increase. Risk factors associated with PC include smoking, heavy alcohol drinking, overweight and obesity, diabetes and chronic pancreatitis. The microbiome of the oral cavity and colon infuence the risk of PС. Approximately 10 % of PC is estimated to have familial inheritance. The risk of PC in patients with inherited syndromes ranges from 2 (hereditary breast and ovarian cancer syndrome) to 132 (Peutz-Jeghers syndrome). Regions of the genome containing variants of single nucleotide polymorphism (SNPs), which are more common in patients with PC than in healthy people, were identifed. The most common somatic mutations include mutations in the driver genes of prostate cancer, which include the KRAS oncogene and tumor suppressor genes TP53, CDKN2A, and SMAD4.The less common mutations of genes include AIB1/NCOA, ERBB2/HER2/EGFR2, AKT2, BRAF, CCND1, RB1, etc. They are identifed as “passenger” mutations although the combined effect of polymorphism of these genes can be signifcant and comparable to the infuence of the driver gene. Conclusion. A signifcant disadvantage of our understanding of the process of carcinogenesis is the lack of information about carcinogenic factors that cause specifc mutations, i.e. the formation of mutational signatures. To solve this problem, in 2017, the international scientifc project GRAND CHALLENGE “Mutograph” was launched. The scientists of the Department of Cancer Epidemiology of N. N. Blokhin National Medical Research Center of Oncology are members of the international team working on this project.